The Values in The Japin Sigam Kotabaru Dance Performance As A Cultural Heritage of The Banjar Coastal Community - Sani, M. Budi Zakia; Handy, Muhammad Rezky Noor; Halimah, Halimah; Solekah, Solekah; Arminah, Arminah; Alif, M. Nur; Ilham, Abdullah Samad (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2026)
This article examines in depth the cultural values manifested and passed down through the Japin Sigam Dance performance in Kotabaru, South Kalimantan. This research is motivated by the importance of documenting the substantive values of traditional dances threatened by globalization. The Japin Sigam Dance is a unique Japin variant originating in the Sigam Kingdom (Pulau Laut) since the 1850s and serves as a dance of respect and social interaction for young men and women bound by religious and customary norms. This research uses a descriptive qualitative method, employing an analytical approach grounded in a systematic literature review and field data. Data collection techniques include observation, interviews, document studies, and documentation. The results and discussion indicate that the cultural values in Japin Sigam are divided into three main aspects: Social Values and Solidarity (reflected in team harmony and respect for guests); Ethical Values and Politeness (embodied in gentle movements, restrained social interactions, and costumes that cover the genitals); and the Values of Wisdom and Life Philosophy (contained in the back-and-forth movements that teach wisdom and adaptation to coastal culture). These values, reinforced by the religious lyrics of Pasisiran songs, reinforce the Banjar cultural identity that must be preserved.